The Indian millennium, AD 1000-2000 - Sabharwal, Gopa (New Delhi Penguin Books, 2000)
The Indian Millennium,AD 1000-2000 is perhaps the most comprehensive and accessible guide that deal with the events and personalities that shaped India over the last one thousand years.Starting with Mahmud of Ghazni;s first expedition into India through t
Keywords: India-History; Millennium